2006
DOI: 10.1111/j.1365-2133.2006.07441.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the number of Merkel cells with the hair cycle in hair discs on rat back skin

Abstract: This difference of the hair cycle dependency between oval and dendritic-type Merkel cells suggests some functional differences, such as a secretory function, related to the hair cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 38 publications
3
30
2
Order By: Relevance
“…Mature Merkel cells are post-mitotic (Moll et al, 1995), but quantitative, morphological and fate-mapping studies suggest that Merkel cells turnover throughout an organism's lifespan (Doucet et al, 2013;Moll et al, 1996;Nafstad, 1987;Nakafusa et al, 2006;Van Keymeulen et al, 2009). These data imply the existence of a Merkel cell precursor that gives rise to new Merkel cells.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mature Merkel cells are post-mitotic (Moll et al, 1995), but quantitative, morphological and fate-mapping studies suggest that Merkel cells turnover throughout an organism's lifespan (Doucet et al, 2013;Moll et al, 1996;Nafstad, 1987;Nakafusa et al, 2006;Van Keymeulen et al, 2009). These data imply the existence of a Merkel cell precursor that gives rise to new Merkel cells.…”
Section: Discussionmentioning
confidence: 81%
“…At P0, the majority of K8+ cells co-expressed K18 and K20, and also took up FM1-43 ( Fig. 5A-C‴ Previous reports suggested that Merkel cell numbers in rodent hairy skin change during the hair cycle (Moll et al, 1996;Nakafusa et al, 2006), so we wondered whether hair cycle stage might affect competency of keratinocytes to respond to Atoh1 induction. Atoh1 induction for 24 h at P24-25 during anagen I followed by tissue harvest 4 days or 2 weeks later resulted in production of ∼55× (P=0.011, t-test) and ∼100× (P=0.004, t-test) more ectopic K8+ cells, respectively, than induction at P19-20 during telogen I (Fig.…”
Section: Atoh1mentioning
confidence: 99%
“…Together with the results found for NGF-R and N-CAM, these data suggest that most MCs in hair follicles are not involved in mechanoreception and are not associated with nerve Wbers. In this context, the presence of dendritic and round MCs in hair follicles (Nakafusa et al 2006) is striking. Moreover, a change of the number of dendritic MCs was observed during the hair cycle, while the amount of round MCs was not altered.…”
Section: Discussionmentioning
confidence: 96%
“…Touch dome keratinocytes have a distinct molecular profile compared with the surrounding epidermis, including expression of keratin 17 (K17) in basal cells (16). There is ongoing cellular turnover in touch domes, with constant production of stratified epithelial keratinocytes and cyclical expansion of terminally differentiated Merkel cells that coincides with anagen regeneration in the hair cycle (17). Genetic fate mapping has shown that the progenitors maintaining these two cell types are found among the K17 + cells in the touch dome (18), with unipotent atonal homolog 1 (Atoh1)-positive progenitors maintaining the Merkel cells (19).…”
mentioning
confidence: 99%